Educating the Hearts of Adolescents: The Role of Islamic Education Psychology in Developing Emotional Intelligence - Lubis, Rayendriani Fahmei (Pascasarjana Universitas KH. Abdul Chalim, 2025)
This article aims to examine the role of Islamic educational psychology in developing adolescents’ emotional intelligence through a spiritual approach rooted in Islamic teachings. The study is based on the assumption that Islamic spiritual values have great potential to shape adolescents’ self-awareness, emotional regulation, and social skills holistically. The rationale for this research stems from the growing emotional challenges faced by adolescents in the modern era, such as academic stress, identity crises, and poor emotional regulation. The subjects of this study were students of Madrasah Aliyah Swasta Al-Ansor, using a qualitative research method and an educational psychology approach. Data collection techniques included interviews, observations, and documentation. The findings show that Islamic education plays a significant role in guiding adolescents to develop emotional intelligence through the internalization of faith-based values, spiritual cultivation, teacher role modeling, and a supportive religious environment. The implications highlight the importance of integrating modern psychological theories with Islamic transcendental values in designing learning strategies and character development programs, enabling adolescents to navigate life’s dynamics with balanced emotional and spiritual strength.